Correlation of Superior Canal Dehiscence Surface Area With Vestibular Evoked Myogenic Potentials, Audiometric Thresholds, and Dizziness Handicap. Issue 8 (September 2016) - Hunter, Jacob B.; O'Connell, Brendan P.; Wang, Jianing; Chakravorti, Srijata; Makowiec, Katie; Carlson, Matthew L.; Dawant, Benoit; McCaslin, Devin L.; Noble, Jack H.; Wanna, George B.
Abstract : Objective: To correlate objective measures of vestibular and audiometric function as well as subjective measures of dizziness handicap with the surface area of the superior canal dehiscence (SCD). Study Design: Retrospective chart review and radiological analysis. Setting: Single tertiary academic referral center. Patients: Preoperative computed tomography imaging, patient survey, audiometric thresholds, and vestibular evoked myogenic potential (VEMP) testing in patients with confirmed SCD. Intervention(s): Image analysis techniques were developed to measure the surface area of each SCD in computed tomography imaging. Main Outcome Measure(s): Preoperative ocular and cervical VEMPs, air and bone conduction thresholds, air-bone gap, dizziness handicap inventory scores, and surface area of the SCD. Results: Fifty-three patients (mean age 52.7 yr) with 84 SCD were analyzed. The median surface area of dehiscence was 1.44 mm 2 (0.068–8.23 mm 2 ). Ocular VEMP amplitudes ( r  = 0.61, p  <0.0001), cervical VEMP amplitudes ( r  = 0.62, p  <0.0001), air conduction thresholds at 250 Hz ( r  = 0.25, p  = 0.043), and air-bone gap at 500 Hz ( r  = 0.27, p  = 0.01) positively correlated with increasing size of dehiscence. An inverse relationship between cervical VEMP thresholds ( r  = −0.56, p  < 0.0001) and surface area of the dehiscence was observed. No association between dizziness handicap and surface area was identified. Conclusion: Among patients with confirmed SCD, ocular and cervical VEMP amplitudes, cervical VEMP thresholds, and air conduction thresholds at 250 Hz are significantly correlated with the surface area of the dehiscence.